FORMULATION AND EVALUATION OF SOLID LIPID NANOPARTICLES CONTAINING CAFFEINE TO TREAT CLINICAL MASTITIS - U, AMRUTHA; B, SUSHMITHA; RUBINA, SHAIK; IRIVENTI, PADMINI (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The objective of the present study was to formulate and evaluate caffeine loaded solid lipid nanoparticles (SLNs) in the treatment of clinical mastitis. Methodology: These were prepared by homogenization technique using cholesterol, tween 80, and chloroform as excipients. Preformulation studies such as ultraviolet spectrophotometry, Fourier transform infrared (FTIR), and differential scanning calorimetry (DSC) were performed for the drug. Entrapment efficiency and in vitro dissolution studies were carried out for prepared SLN’s and the optimum formulation (F2) was taken for further studies such as FTIR, DSC, scanning electron microscopy, particle size, and zeta potential analysis. Results: Obtained results stated that prepared SLNs are roughly spherical in nature and are in nanorange. These were incorporated in Carbopol gel and further evaluation studies such as pH, spreadability, viscosity, homogeneity, and in vitro drug diffusion studies were carried out. All the results obtained state that prepared nanogel has shown sustained release of drug. The antimicrobial study was carried out using Staphylococcus aureus and it was confirmed by appearance of the zone of inhibition. Conclusion: Nanogel that contains Caffeine SLNs with 1:2 ratio drug:lipid has shown good in vitro release. Sustained release of Caffeine drug till 12 h was achieved by delivering it in the form of nanogel.